Obecność i uwaga podczas zajęć online – rozważania o potrzebnie nowych definicji na podstawie badań ankietowych - Karolina Zioło-Pużuk (Edukacja Ustawiczna Dorosłych)
The article presents results of surveys conducted among graduates of online workshops for teachers. Respondents were asked about factors positively and negatively influencing engagement during classes and attendance. The study showed, among other things, during classes attendees also performed other activities not related to participation in the workshops, and yet they highly assessed their commitment and work efficiency. Moreover, since they were logged in all the time during classes, it was assumed that they were present. This indicates that there is a need to ask a question about what “attendance” during online classes is, how it differs from attendance during face-to-face classes and how it should be assessed and monitored. The article attempts, based on original research and scientific papers review, to present the question of online attendance in more detail and to describe possible practical solutions helping in maintaining high attendance and attention during online classes.